ANOMALY VARIATIONS OF TEMPERATURE FIELDS AND ITS RELATIONSHIP WITH ENSO PHENONMENON IN NINH THUAN - BINH THUAN WATERS - Chung, Tran Van; Huan, Nguyen Huu; Long, Bui Hong; Hoi, Nguyen Truong Thanh; Bac, Phan Thanh (Vietnam Journal of Marine Science and Technology, 2018)
In this paper, our aim was to examine the role of ENSO in the recent climate variations. Analyzed results on temporal variability of thermal fields in period of 38 years (Jan. 1979-Aug. 2016) showed that Ninh Thuan - Binh Thuan waters were subjected to the significant impact of the ENSO phases (warming and cooling) as well as other processes related to seasonal, inter-seasonal, yearly and mutlti-yearly variations such as in the periods 1986-1989, 1996-2000 and 2009-2011. In order to clarify above issues, authors carried out the analysis of the temporal -spatial changes of temperature fields (include air temperature and sea surface temperature) in Ninh Thuan - Binh Thuan region. The temperature data were exploited from The National Centers for Environmental Prediction (NCEP) and Climate Forecast System Reanalysis (CFSR) in the form of hourly time-series products with spatial resolution of 0.3o (1979-2010) and 0.20o (2011-8/2016). The results showed that 2016 was quite similar to 1998 and 2010 when the coral bleaching occurred in the study area.